Resident work hours: why keeping the status quo may not be such a bad thing - Razik, Roshan; Slessarev, Marat (Revue canadienne de l'éducation médicale, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-CA JA X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-ansi-language:EN-CA; mso-fareast-language:EN-CA;} --> <!--[endif] --><span style="font-size: 10.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; color: #111111; background: white; mso-ansi-language: EN-CA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-CA">Resident duty hours have become an increasingly debated topic in post-graduate medical education. Work-hour restrictions have been implemented for first-year residents in the US and more recently for all residents in Quebec. Current and future work-hour rules affect a variety of stakeholders: government, hospitals, residency training programs, patients, and most of all residents. In this article, we hope to examine the issue from a Canadian perspective and delineate some of the reasons why changing the current call structure may have potentially deleterious effects to all those concerned.